Performance improvement of hybrid subcarrier multiplexing optical spectrum code division multiplexing system using spectral direct decoding detection technique - Sahbudin, Ratna Kalos Zakiah; Abdullah , Mohamad Khazani; Mokhtar, Makhfudzah (Elsevier, 2009)
This paper proposes a hybrid subcarrier multiplexing/optical spectrum code division multiplexing (SCM/OSCDM) system for the purpose of combining the advantages of both techniques. Optical spectrum code division multiple-access (OSCDMA) is one of the multiplexing techniques that is becoming popular because of the flexibility in the allocation of channels, ability to operate asynchronously, enhanced privacy and increased capacity in bursty nature networks. On the other hand, subcarrier multiplexing (SCM) technique is able to enhance the channel data rate of OSCDMA systems. In this paper, a newly developed detection technique for the OSCDM called spectral direct decoding (SDD) detection technique is compared mathematically with the AND subtraction detection technique. The system utilizes a new unified code construction named KS (Khazani–Syed) code. The results characterizing the bit-error-rate (BER) show that SDD offers a significant improved performance at BER of 10−9.